Is this glove and boot protective: unraveling the mystery? - Damodaran, Devi; Rajagopalan, Rajesh; Vethanayagam, Mohankumar; Kandasamy, Revathi (International Journal of Research in Dermatology, 2024)
Pellagroid dermatitis, a rare manifestation of niacin deficiency exacerbated by chronic alcoholism, presents with distinct cutaneous and systemic symptoms. We report a case of a 42-year-old male with a history of daily alcohol consumption and heavy smoking, presenting with characteristic skin lesions predominantly over sun-exposed areas. The patient exhibited a spectrum of symptoms including dermatological manifestations, gastrointestinal disturbances, and neuropsychiatric symptoms. Diagnostic workup revealed hypoalbuminemia, mild elevated CRP, and microcytic hypochromic anemia, consistent with niacin deficiency. Treatment included niacinamide supplementation, B12 injections, proton pump inhibitors, and psychiatric counseling. Long-term management is essential to prevent relapse and associated complications.